Analisis Kebutuhan Penyusunan Code of Conduct dan Pedoman Etika Standar Publikasi Humas Pt Ka Properti Manajemen - Shintya Dewi Afifah; Rici Tri Harpin Pranata (Journal of Creative Student Research, 2026)
Digital communication that continues to evolve requires every organization to have structured communication governance, because without clear standards, message consistency, information credibility, and corporate reputation become difficult to maintain. This is especially critical for companies operating within an integrated corporate ecosystem, where alignment of identity and inter-institutional publication standards is essential.PT KA Properti Manajemen, as a subsidiary of PT Kereta Api Indonesia (Persero), directly faces this challenge. Although the parent company’s publication standards serve as a reference, the communication characteristics of PT KA Properti Manajemen—shaped by its specific business sector, audience segmentation, and digital dynamics—require more operational and contextual guidelines. This study aims to analyze the need for developing a Code of Conduct and to formulate Ethical Guidelines and Public Relations Publication Standards as instruments of corporate communication governance. It employs a qualitative descriptive approach using a case study method, including field observations, semi-structured interviews, document review, and literature study. The findings indicate that the parent company’s standards function as general guidelines that do not fully address operational needs at the subsidiary level. Therefore, the Code of Conduct development process is carried out in an adaptive manner by considering communication ethics, visual identity usage, social media governance, and accountable publication mechanisms. This results in guidelines that are not merely administrative rules, but a strategic instrument to strengthen communication consistency and corporate identity.